Post-Socialist Ethnic Symbolism, Suppression of Yugoslav Social Memory, and Radical Populism Psychology - Faruk Hadžić (Journal of Economy Culture and Society)
The paper argues that post-socialist neoliberal democracy is hindered by the exposed or conditioned ethnic symbolic radical populism, particularly in the post-Yugoslav ethnonationalism political behavior. Moreover, the approach toward the fascist ideology symbols disregards the communist social memory of stability and human security and a collectivism-oriented community. Neoliberal globalization has strengthened national identities, supported by the war-related creation of ethnic homogenous territories. Consequently, former Yugoslavia’s historical conflicting memory cultures from WW2 to the Yugoslav wars present enduring processes within sociopolitical ethnic-religious traditions. The collective historical and social memory that forms people’s identities is manipulated, falsified, reduced, and politically instrumentalized. Contemporary ethnic-symbolic politics communicate through conservative political orientations: re-traditionalism behavior (including some left-wingers) advocates public acceptance. Historical anti-fascism actors have been stigmatized within attitudes toward fascist ideology symbolism and traditional Balkan sociopolitical mythologies. Frequent use of (often) antagonistic ethnic symbolism in textual, rhetorical and visual forms expresses it. Various methods of conducting historical revisionism in the symbolic and ideological vocations decrease Yugoslavia’s social memory. Institutional and non-institutional engagement is normatively needed in a battle for correct memory. Citizens’ participation in political decision-making outside the ethnoreligious paradigm is crucial. The consequence of populist political orders in ethnoreligious partitioned post-socialism is ethnic-symbolic collectivism. It oppresses individual identity and excludes the possibility of distinct classification. Contemporary notions of autonomy and mind, adapted to modern society, provide a theoretical framework for formulating political strategies in a post-national context. Acquisitive components of civil society and the society’s stagnation due to slow consolidation can abruptly transform into political apathy motivating violent disorder. Accordingly, many sociopolitical realities symbolize and indicate that "democratized" post-socialist and post-Yugoslav states are more "inadequate" and "ineffective" than Yugoslavia.